A mixed-methods systematic review of patients' experience of being invited to participate in surgical randomised controlled trials. (May 2020) - Phelps, Emma Elizabeth; Tutton, Elizabeth; Griffin, Xavier; Baird, Janis
Abstract: Rationale: Randomised controlled trials (RCTs) of surgical interventions are increasing. Such trials encounter challenges that are not present in RCTs of non-surgical interventions because of the nature of the intervention. Several studies have explored patients' experiences of surgical trials to improve recruitment or identify barriers and facilitators to research in this setting. Synthesizing these studies may reveal further insights or confirm whether saturation of relevant themes has been achieved. Objective: This review aimed to understand the experiences of adults who are invited to participate in surgical RCTs. Method: MEDLINE, Web of Science, and CINAHL were searched to identify articles meeting the inclusion criteria. Assessment of quality was conducted with studies given an overall quality rating of good, fair, or poor. A segregated approach was used to synthesize the data. This method included a thematic synthesis of the qualitative data and a narrative review of the quantitative data. The findings of both syntheses were then integrated. Results: Thirty-four articles reporting 28 trials were included. This review found that the decision to participate in a surgical trial is influenced by multiple factors including patients' individual circumstances and attitudes, and the characteristics of the trial itself. The study identified three themes which encompass both qualitative and quantitative findings. These themes reveal it was important for patients to i) make sense of the trial and trial processes, ii) weigh up the risks and benefits of their different treatment options and participation, and iii) trust the trial and staff. Conclusions: A patient-centred approach to trial recruitment may help staff build trusting relationships with patients and address their individual concerns about the trial and the risks and benefits of participation. Highlights: A mixed-methods review of patients' experience of participation in surgical trials. Some patients do not find randomisation an acceptable way to allocate treatment. Multiple factors influence how patients consider whether to participate. Trust is influences patients decision to participate. A patient-centred approach addressing patients' individual concerns is recommended.